Accounting information for decisions - Ingram, Robert W.; Albright, Thomas L.; Baldwin, Bruce A.; Hill, John W. (Australia : Thomas / South-Western, 2005)
Business
2005-02-22
Keywords: Accounting; Accounting information; Financial accounting; Managerial accounting; Cost evaluation